I-Witness poor children a postcolonial criticism of I-Witness? representation of children in poverty - Narvaez, Alyza Joy Ventura 1991- (2012)
"Children in poverty has been one of the themes in I-Witness documentaries, a weekly television documentary in GMA 7. This study examines the representations of Filipino children in poverty in selected I-witness documentaries: boy pusit, Bakas ng paa, Nanay na si Nene, Buto't Balat ,Ambulansyang de Paa, Uuwi na si Udong, Batang Langoy, and Batang Kalabaw.It attempts to uncover ideologies embedded in the images and language represented by these documentaries. To attain this objective, textual analysis- through the aid of semiotics and discourse analysis - is used to examine the representations of two important constructions, namely childhood and the Third World, that shape the representation of children in poverty in the selected documentaries."